Humans, animals, things and animacy - Bayanati, S. (Shiva); Toivonen, I. (Ida) (Open Linguistics, 2019)
Animacy influences the patterns of subject-verb agreement marking in many languages, including Persian and Inari Saami. In Persian, animate plural subjects trigger plural agreement on the verb, whereas inanimate subjects may or may not trigger agreement. The variation is governed by factors such as personification, agency and distributivity. In Inari Saami, verbs fully agree with human subjects and verbs partially agree with inanimate subjects. Verbs may or may not agree with subjects referring to animals. We argue that the intricate interaction between biological animacy and grammatical agreement in these two languages warrants careful consideration of the tripartite distinction between biological animacy in the world, our conceptualization of animacy and formal animacy features in the grammar.